PENERAPAN QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK PENINGKATAN KINERJA INDUSTRI AMPLANG BERDASARKAN KEPUASAN PELANGGAN - Nina Hairiyah; Mariatul Kiptiah; Bella Krestinawiyati Fituwana (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Tanah Laut Regency, which is the center of tourism in South Kalimantan, has one of the superior products that are commonly used as souvenirs, namely amplang products. Currently, the competition for amplang products is getting stronger with the increasing number of amplang industries in Tanah Laut Regency, so a study is needed so that the Melati Group Amplang Industry can survive and compete. This study aims to determine what attributes affect the buyer's decision to buy amplang products, measure the level of satisfaction and consumer interests and identify strategic planning for improving the quality performance of amplang products using the Quality Function Deployment (QFD) method. This research was conducted in Takisung District, Tanah Laut Regency, using descriptive methods and a survey approach. The data collection technique was done by interviewing the VOC (Voice of Customer) through questionnaires and literature study. The data in this study were analyzed using the Quality Function Deployment (QFD). Based on the results of research conducted using the QFD method, there are 15 product attributes desired by consumers and translated into 8 technical responses in the House of Quality (HOQ). The level of customer importance to UD Kelompok Melati amplang product with the greatest value was the completeness of the packaging information attribute (4.40) and the importance level with the smallest value was the appropriate color attribute (3.67). The highest level of customer satisfaction with Amplang products is the price attribute that matches the quality (4.23), and the smallest level of satisfaction is the appropriate color attribute (3.60). Meanwhile, steps to improve the quality performance of amplang products, get priority attributes and technical response performed by SMEs (maintaining a distinctive and strong spice formula, selecting the quality of mackerel fish, speed of customer response, employee coterbuatordination and appropriate product selling prices).